Osteocytes contribute via nuclear receptor PPAR-alpha to maintenance of bone and systemic energy metabolism - Chougule, Amit; Baroi, Sudipta; Czernik, Piotr J.; Crowe, Emily; Chang, Mi Ra; Griffin, Patrick R.; Lecka-Czernik, Beata (Frontiers in Endocrinology, 2023)
Introduction The view that bone and energy metabolism are integrated by common regulatory mechanisms is broadly accepted and supported by multiple strands of evidence. This includes the well-characterized role of the PPARγ nuclear receptor, which is a common denominator in energy metabolism and bone metabolism. Little is known, however, about the role of PPARα nuclear receptor, a major regulator of lipid metabolism in other organs, in bone. Methods A side-by-side comparative study of 5-15 mo old mice with global PPARα deficiency (αKO) and mice with osteocyte-specific PPARα deficiency (αOTKO) in order to parse out the various activities of PPARα in the skeleton that are of local and systemic significance. This study included transcriptome analysis of PPARα-deficient osteocytes, and analyses of bone mass and bone microarchitecture, systemic energy metabolism with indirect calorimetry, and differentiation potential of hematopoietic and mesenchymal bone cell progenitors. These analyses were paired with in vitro studies of either intact or silenced for PPARα MLO-A5 cells to determine PPARα role in osteocyte bioenergetics. Results In osteocytes, PPARα controls large number of transcripts coding for signaling and secreted proteins which may regulate bone microenvironment and peripheral fat metabolism. In addition, PPARα in osteocytes controls their bioenergetics and mitochondrial response to stress, which constitutes up to 40% of total PPARα contribution to the global energy metabolism. Similarly to αKO mice, the metabolic phenotype of αOTKO mice (both males and females) is age-dependent. In younger mice, osteocyte metabolism contributes positively to global energetics, however, with aging the high-energy phenotype reverts to a low-energy phenotype and obesity develops, suggesting a longitudinal negative effect of impaired lipid metabolism and mitochondrial dysfunction in osteocytes deficient in PPARα. However, bone phenotype was not affected in αOTKO mice except in the form of an increased volume of marrow adipose tissue in males. In contrast, global PPARα deficiency in αKO mice led to enlarged bone diameter with a proportional increase in number of trabeculae and enlarged marrow cavities; it also altered differentiation of hematopoietic and mesenchymal marrow cells toward osteoclast, osteoblast and adipocyte lineages, respectively. Discussion PPARα role in bone is multileveled and complex. In osteocytes, PPARα controls the bioenergetics of these cells, which significantly contributes to systemic energy metabolism and their endocrine/paracrine function in controlling marrow adiposity and peripheral fat metabolism.